1989
DOI: 10.3109/00498258909042314
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Metabolites of Rifabutin, a New Antimycobacterial Agent, in Human Volunteers

Abstract: 1. Metabolites of the antimycobacterial agent 4-deoxo-3,4-[2-spiro-(N-isobutyl-4-piperidyl)]-(1H)-imidazo-(2,5-dihydro )- rifamycin S (rifabutin) were isolated from human urine after administration of a single oral dose of the drug. Some of these metabolites were identified by direct inlet mass spectrometry, 1H-n.m.r. spectrometry and, in two cases, by chromatographic comparison with reference compounds. 2. Unchanged drug, 25-O-deacetyl rifabutin and four other metabolites were identified in human urine. 25-O-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…The precise metabolic pathways for rifabutin are controversial, with in vitro data supporting both microsomal 22 and nonmicrosomal metabolism. 23 In this study, we found that indinavir increased 25-desacetyl rifabutin concentrations more than rifabutin concentrations (Table II).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The precise metabolic pathways for rifabutin are controversial, with in vitro data supporting both microsomal 22 and nonmicrosomal metabolism. 23 In this study, we found that indinavir increased 25-desacetyl rifabutin concentrations more than rifabutin concentrations (Table II).…”
Section: Discussionmentioning
confidence: 99%
“…However, rifampin is a potent inducer of cytochrome P450 (CYP) enzymes [9][10][11][12][13][14] and is therefore contraindicated in patients taking HIV protease inhibitors because it may reduce protease inhibitor concentrations by as much as 80% to 90%. 22 The primary routes of metabolism are desacetylation and oxidation; however, the CYP450 enzymes involved (in vitro) have not been elucidated, and metabolism may be nonmicrosomal. [15][16][17][18] In 3 large placebo-controlled trials in HIV-infected patients, rifabutin substantially decreased the incidence of MAC bacteremia and reduced the signs and symptoms associated with disseminated disease.…”
mentioning
confidence: 99%
“…Autoinduction Properties ofRifibutin and Rifampicin in Humans RIB is metabolized in humans to more than 20 compounds (44). Besides the unchanged drug, 25-O-deacetyl RIB has been identified in human urine together with four metabolites produced by oxidative pathways: 31-OH-RIB, 32-OH-RIB, 32-OH-25-O-deacetyl-RIB and 25-0-deacetyl-RIB-piperidine-N-oxide.…”
Section: Inducton Properties Of Rifampicin and Rifabutin In Animalsmentioning
confidence: 99%
“…!3] These are 25-0-deacetylrifabutin and 31-hydroxy-rifabutin. In addition to these 2 metabolites, at least 4 other metabolites have been identified in the urine:[58,59] 32-hydroxyrifabutin, 32-hydroxy-25-0-deacetyl-rifabutin, 25-0-deacetyl-rifabutin-N-oxide, and 30-hydroxy-rifabutin. In addition, other metabolites of undetermined structure have been isolated.…”
mentioning
confidence: 98%